Mechanical properties of paraffin treated wood - Esteves, B. (2013)
Paraffin has been used throughout the ages as surface protection of wood. Its use by impregnation to improve resistance to biodegradation is recent. This study was intended to determine the improvements of main mechanical properties of wood with this treatment. The wood used in the tests was healthy wood of Pinus pinaster Ait. The wood was impregnated with paraffin at different levels, using a hot-cold process, with dry and moist wood, with 2h in a hot bath at 160°C and 10 or 30 min in a water bath at 70°C. Weight gain, bending strength and bending stiffness (MOE) were determined using a universal testing machine by a 3 points essay. The Janka hardness was also determined. As expected, the moist wood absorbed more paraffin with weight gains between 72% and 100%. The dry wood presented weight gains between 46% and 51%. The bending strength (MOR) increased with the increase in paraffin, reaching a 39% increase compared to untreated wood for wood with a weight gain of about 80%. In relation to MOE, there was also an increase, but smaller, reaching about 13% for wood with a weight gain around 80%. The Janka hardness increased significantly with the weight gain, reaching about 40% for wood with 80% weight gain. In conclusion the impregnation should not be made with completely dry wood and, in addition to the known resistance to biodegradation; the treatment also improves several mechanical properties like bending strength, bending stiffness and hardness which might increase the wood value